Subcutaneous phaeohyphomycosis in an immunocompetent Individual: A case report - Sudharani Chintagunta; Geetakiran Arakkal; Sudha V Damarla; Akshay K Vodapalli (Wolters Kluwer Medknow Publications, 2017)
Phaeohyphomycosis is a rare mycotic infection caused by various heterogenous groups of phaeoid (dematiaceous) fungi involving the skin and subcutaneous tissue. Common clinical manifestations are subcutaneous abscesses or cystic swellings. Here, we report a case of subcutaneous phaeohyphomycosis presenting as multiple asymptomatic cystic swellings over the hands and feet without any predisposing factors. Histopathology showed granulomatous inflammation and special stain with Grocott's methanamine silver stain revealed broad pigmented hyphae. Culture showed black-colored colonies identified as Exophiala jeanselmi. The patient was treated with surgical excision of the lesions.